Angiographic results of retinal-retinal anastomosis and retinal-choroidal anastomosis after treatments in eyes with retinal angiomatous proliferation - Saito M; Iida T; Kano M; Itagaki K (Clinical Ophthalmology, 2012)
Masaaki Saito,1 Tomohiro Iida,1,2 Mariko Kano,1 Kanako Itagaki11Department of Ophthalmology, Fukushima Medical University School of Medicine, Fukushima, 2Department of Ophthalmology, Tokyo Women's Medical University School of Medicine, Tokyo, JapanBackground: The purpose of this study was to evaluate the angiographic results of retinal-retinal anastomosis (RRA) and retinal-choroidal anastomosis (RCA) for eyes with retinal angiomatous proliferation (RAP) after treatment with intravitreal bevacizumab injections as monotherapy or intravitreal bevacizumab combined with photodynamic therapy.Methods: In this interventional, consecutive case series, we retrospectively reviewed five naïve eyes from four patients (mean age 80 years) treated with three consecutive monthly intravitreal bevacizumab (1.25 mg/0.05 mL) injections as initial treatment, and followed up for at least 3 months. In cases with over 3 months of follow-up and having recurrence of RAP or leakage by fluorescein angiography, retreatment was performed with a single intravitreal bevacizumab injection and photodynamic therapy.Results: Indocyanine green angiography showed RRA in three eyes with subretinal neovascularization and RCA in two eyes with choroidal neovascularization at baseline. At 3 months after baseline (month 3), neither the RRA nor RCA was occluded in any eye on indocyanine green angiography. Retreatment with intravitreal bevacizumab plus photodynamic therapy was performed in three eyes at months 3 (persistent leakage on fluorescein angiography), 6, and 7 (recurrence of RAP lesion), which achieved obvious occlusion of the RRA and RCA. Mean best-corrected visual acuity improved from 0.13 to 0.21 at month 3 (P = 0.066). No complications or systemic adverse events were noted.Conclusion: Although intravitreal bevacizumab for RAP was effective in improving visual acuity during short-term follow-up, intravitreal bevacizumab could not achieve complete occlusion of RRA and RCA, which could lead to recurrence of a RAP lesion and exudation. Retreatment with intravitreal bevacizumab plus photodynamic therapy ultimately achieved complete occlusion of the RRA and RCA.Keywords: retinal angiomatous proliferation, retinal-retinal anastomosis, retinal-choroidal anastomosis, bevacizumab, photodynamic therapy, ranibizumab